CHL1 Is Expressed and Functions as a Malignancy Promoter in Glioma Cells - Yang, Zhai; Xie, Qing; Hu, Cheng-Liang; Jiang, Qiong; Shen, Hui-Fan; Schachner, Melitta; Zhao, Wei-Jiang (Frontiers in Molecular Neuroscience, 2017)
The cell adhesion molecule with homology to L1CAM (close homolog of L1) (CHL1) is a member of the cell adhesion molecule L1 (L1CAM) gene family. Although CHL1 expression and function have been reported in several tumors, the roles of CHL1 in the development of glioma remains unclear. In the present study, we investigated the effects of CHL1 on proliferation indexes and activation of Akt1 and Erk signaling by siRNA in U-87 MG human glioblastomas and human U251 and SHG-44 glioma cells. We found that siRNA targeting CHL1 significantly down-regulated the expression of CHL1 mRNA and protein accompanied by reduced cell proliferation and transmigration invasion in all three cell lines. Down-regulating CHL1 expression also reduced cell survival, as measured by the Bcl-2/Bax ratio, and increased activation of caspase-3. In subcutaneous U-87 MG cell xenograft tumors in nude mice, intratumoral administration of siRNA targeting CHL1 treatment significantly down-regulated CHL1 expression in vivo, accompanied by increased levels of activated caspase-3. Our combined results confirmed for the first time that in contrast to findings about CHL1 in most other cancer types, CHL1 functions in promoting cell proliferation, metastasis and migration in human glioma cells both in vitro and in vivo. These results indicate that CHL1 is a therapeutic target in the clinical management of glioma/glioblastoma.